2014
DOI: 10.1093/plankt/fbu009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poor manageability and low nutritional value of cyanobacteria on Daphnia magna life history performance

Abstract: Cyanobacteria may reduce Daphnia fitness through their toxicity, low nutritional value or poor manageability. In this study, the relative importance of the low nutritional value and poor manageability of cyanobacteria on Daphnia life history were determined. To separate these two aspects of cyanobacteria impact, short or long filaments of Cylindrospermopsis raciborskii were given as food to five clones of Daphnia magna either alone or together with the green alga Scenedesmus obliquus. Feeding with short cyanob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 55 publications
1
53
1
Order By: Relevance
“…This research demonstrated that D. magna does indeed have a certain feeding rate on filamentous algae such as M. granulata and Oscillatoria sp., supporting the view that daphnids can grow and reproduce on a diet dominated by filamentous cyanobacteria (Repka 1998). Furthermore, the treatment groups which contained a small quantity of good quality food (S. obliquus) showed higher carbon and nitrogen isotopic turnover rates driven by both growth and metabolism (k þ m) relatively, demonstrating that the poor nutritional value of filamentous algae could be completely overcome by supplementation (Bednarska et al 2014).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This research demonstrated that D. magna does indeed have a certain feeding rate on filamentous algae such as M. granulata and Oscillatoria sp., supporting the view that daphnids can grow and reproduce on a diet dominated by filamentous cyanobacteria (Repka 1998). Furthermore, the treatment groups which contained a small quantity of good quality food (S. obliquus) showed higher carbon and nitrogen isotopic turnover rates driven by both growth and metabolism (k þ m) relatively, demonstrating that the poor nutritional value of filamentous algae could be completely overcome by supplementation (Bednarska et al 2014).…”
Section: Discussionsupporting
confidence: 53%
“…Other research showed that the weight-specific ingestion rates of D. magna were higher on the shorter Oscillatoria filaments than on the longer ones (Gulati et al 2001). Furthermore, cyanobacteria can shape microevolutionary changes in Daphnia populations (Bednarska et al 2014). It was also observed that the filaments of both Melosira and Oscillatoria were inadequate food source for Daphnia because they could not sustain growth and reproduction of planktonic animals as well as unicellular algae could not sustain growth and reproduction of planktonic animals as well as unicellular algae, such as Scenedesmus (Porter & Orcutt 1980;Haney 1987;Lampert 1987;DeBernardi & Giussani 1990;Bednarska et al 2014).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar trend was reported by Oberhaus et al (2007), who found that Daphnia pulicaria Forbes is capable of effective grazing only on short (50-100 µm) filaments of Planktothrix rubescens De Candolle ex Gomont. Quite recently, Bednarska et al (2014) provided evidence that the consequences of the filament length for Daphnia can be manifested throughout the lifetime of these organisms. Daphnids exposed to longer (>50 µm) filaments of Cylindrospermopsis raciborskii (Woloszynska) Seenayya & Subba Raju were smaller in size at the first reproduction and had a lower fecundity than the animals that fed on filaments shorter than 50 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers revealed that Daphnia could abort eggs when filamentous cyanobacteria were present, and this phenomenon intensified at higher temperatures (Bednarska and Slusarczyk 2013). Bednarska with coworkers also found evidence that reduction of Daphnia fitness in response to cyanobacterial filaments strongly depends on filaments length (Bednarska et al 2014). According to the aforementioned study, long filaments ([50 lm) caused a greater reduction in somatic growth and fecundity in most clones of D. magna, in comparison with short filaments (\50 lm).…”
Section: Introductionmentioning
confidence: 83%